Hubungan Sumber Air Bersih dan Sumber Air Minum dengan Kejadian Diare Pada Balita di Puskesmas Sidomulyo Kota Pekanbaru - Sari, Tyagita Widya; Annisa, Rizka (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Diarrhea is a change in shape and consistency of soft stools until it melt and increases the frequency of defecation more than usual, which is 3 or more time a day. Diarrhea is a major cause of pain and death in children. Diarrhea can be influenced by several factor, including clean water and drinking water sources. Clean water and drinking water sources that do not meet the requirements can increase the risk for people with diarrhea in the community. Sidomulyo Health Center has the fifth highest incidence of diarrhea in children of 21 health center in Pekanbaru City in 2017 as many as 188 cases (8,33%). The objective of this study was to determine the relationship between clean water and drinking water sources with diarrhea of toddler in Sidomulyo Health Center Pekanbaru. This research used an analytic observational with a cross sectional study design. This research was conducted on a population of toddler in Pekanbaru City on August to September 2018. The sampling technique was carried out by accidental sampling with a sample size of 51 respondents. Data analysis was conducted through chi square's test for p-value. There was no relationship between clean water sources (p-value = 0.219) and drinking water sources (p-value = 0.439) with diarrhea of toddler. Clean water and drinking water sources are not related with diarrhea of toddler in Sidomulyo Health Center Pekanbaru.